PENGETAHUAN TENTANG PENDIDIKAN SEKS PADA ANAK USIA 4-6 TAHUN OLEH ORANG TUA DAN GURU DI KECAMATAN TAMPAN KOTA PEKANBARU - Nurhidayati Nurhidayati; Devi Risma; Yeni Solfiah (Program Studi Pendidikan Guru PAUD Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2019)
This research is a quantitative research with comparative approach to identify whether there is asignificant difference between knowledge about sex education to 4 to 6 year-old children by parents and of which byteachers in Tampan District, Pekanbaru City, as well as to find out parents’ difficulties in sex education in the aspect ofknowledge. The population of this research was parents and teachers in Tampan District, Pekanbaru City, then 95parents and 95 kindergarten teachers were selected as the research sample using simple random sampling. The datacollection technique was using a test consisting or a set or questions to measure the knowledge. The data analysis wasusing differential test “t” of 2 samples by the help of BM SPSS Statistics for window. The results show that there is avery significant difference between knowledge about sex education to 4-6 year-old children by parents and of which byteachers in Tampan District, Pekanbaru City. The level of knowledge about sex education by parents is 55,78% andcategorized good. Meanwhile, the level of knowledge about sex education by teachers is 69,87% and categorized good.Parents and teachers have different knowledge about sex education in which parents’ knowledge is in the sufficient tolow category seen from the whole indicators. Meanwhile, teachers’ knowledge is in the good category seen from thewhole indicators.